The Integration of the Post-Soviet Countries as a Major Factor in their Global Competitiveness - V. Bainev (Евразийская интеграция: экономика, право, политика, 2019)
The article proves that integration, cooperation, complementarity of capital and scarce resources as the main global trend, leading to the achievement of global competitiveness in the XXI century. Today adopt the doctrine of economic integration is the prerequisite for the survival and progress of the Eurasian Economic Union, established in order to preserve economic and political sovereignty which was formed by its peoples and countries.